2010
DOI: 10.1007/s00436-010-1986-8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance phenomena to amitraz from populations of the ectoparasitic mite Varroa destructor of Argentina

Abstract: In Argentina, Varroa destructor resistance to coumaphos has been previously reported. However, the status of mite susceptibility to other hard acaricides is still unknown. At present, high infestation levels of V. destructor are being detected in colonies of Apis mellifera after treatment with amitraz. The aim of the present study was to determine the LC(50) of amitraz in V. destructor from three apiaries with high mite density after treatment with the acaricide. The LC(50) values were 3.9, 3.5, and 3.7 μg/Pet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 17 publications
0
43
0
3
Order By: Relevance
“…In another approach, Niu et al (2011) demonstrated that propolis extracts reduce toxicity of mycotoxins. All these pieces of work demonstrated that it is imperative to find alternative ways of pesticide usage and attenuate the emergence of resistant plagues (Maggi et al 2010b). This work offers a new tool for beekeepers and researchers for developing an innovative and environmentally friendly management of honey bee colonies.…”
Section: Discussionmentioning
confidence: 99%
“…In another approach, Niu et al (2011) demonstrated that propolis extracts reduce toxicity of mycotoxins. All these pieces of work demonstrated that it is imperative to find alternative ways of pesticide usage and attenuate the emergence of resistant plagues (Maggi et al 2010b). This work offers a new tool for beekeepers and researchers for developing an innovative and environmentally friendly management of honey bee colonies.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the control of such parasites is highly dependent on the application of such synthetic acaricides products as coumaphos (organophosphate), amitraz (formamidine), fluvalinate and flumethrin (pyrethroids), which are all molecules commonly used in beekeeping. The indiscriminate and wrong use of these acaricides has produced a strong selection pressure on different populations of mites, which has led to the emergence of pockets of resistance in different parts of the world (Elzen & Westervelt, 2002;Maggi et al, 2009Maggi et al, , 2010. Additionally, synthetic acaricides can produce unwanted effects on bee colonies such as mortality and replacement of queen bees and poisoning of breeding and adult individuals (Maggi et al, 2013).…”
mentioning
confidence: 99%
“…In Argentina (as in many other parts of the world), the use of synthetic acaricides is being restricted due to the emergence of resistant mite populations (Maggi et al 2009(Maggi et al , 2010a(Maggi et al , 2011Sammataro et al 2005), as well as honey and wax contamination Wallner 1999;Medici et al 2015). Oxalic acid is a natural constituent of honey; values between 8 and 17,000 mg/kg have been found in different honeys (Mutinelli et al 1997;Bernardini and Gardi 2001;Bogdanov et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, resistance to acaricides has become a major problem in the control of mite populations. Increased tolerance to the most widely used synthetic active ingredients has been observed (Maggi et al 2010a(Maggi et al , 2011. Because of the resistance to acaricides, there is a renewed interest in Argentina for substances of natural origin, such as essential oils and their components or organic acids, especially formic acid and oxalic acid (Eguaras et al 2001(Eguaras et al , 2003Maggi et al 2010b;Ruffinengo et al 2014).…”
Section: Introductionmentioning
confidence: 99%